2014
DOI: 10.1371/journal.pone.0089374
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Signature of a Heat-Stable, Chimeric Human Alkaline Phosphatase with Therapeutic Potential

Abstract: Recombinant alkaline phosphatases are becoming promising protein therapeutics to prevent skeletal mineralization defects, inflammatory bowel diseases, and treat acute kidney injury. By substituting the flexible crown domain of human intestinal alkaline phosphatase (IAP) with that of the human placental isozyme (PLAP) we generated a chimeric enzyme (ChimAP) that retains the structural folding of IAP, but displays greatly increased stability, active site Zn2+ binding, increased transphosphorylation, a higher tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 50 publications
3
79
0
4
Order By: Relevance
“…Human ALP consists of a group of isozymes, placental, intestinal and three major tissue-nonspecific isoforms [3], which are encoded by 4 main gene loci: tissue-nonspecific, intestinal, placental, and germ-cell ALP [4][5][6]. Tissue-nonspecific boneand liver-type ALP are formed through posttranslational modifications and differences in carbohydrate composition, leading to different clinical phenotypes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Human ALP consists of a group of isozymes, placental, intestinal and three major tissue-nonspecific isoforms [3], which are encoded by 4 main gene loci: tissue-nonspecific, intestinal, placental, and germ-cell ALP [4][5][6]. Tissue-nonspecific boneand liver-type ALP are formed through posttranslational modifications and differences in carbohydrate composition, leading to different clinical phenotypes [4].…”
Section: Introductionmentioning
confidence: 99%
“…This chimeric construct consists of the crown domain of placental AP, which is incorporated into the intestinal AP structure to improve enzyme stability, while maintaining its catalytic function [24]. Recently published in vitro data confirmed the dephosphorylating capacity of recAP towards LPS and ATP [24].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…This chimeric construct consists of the crown domain of placental AP, which is incorporated into the intestinal AP structure to improve enzyme stability, while maintaining its catalytic function [24]. Recently published in vitro data confirmed the dephosphorylating capacity of recAP towards LPS and ATP [24]. Our preliminary in vitro results demonstrated that recAP can attenuate LPS-induced cytokine production in a human renal cell line [25], whereas recAP improves renal blood flow and vascular resistance and inhibits various parameters of renal inflammation and tissue damage during AKI induced by ischemia-reperfusion or by LPS injection in vivo [26].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…No homem e nos primatas superiores, três isoformas distintas têm sido identificadas: a da placenta, a do intestino e a do fígado-osso-rim (Lowe et al, 1990;Le Du et al, 2001;Le Du e Millán, 2002;Kiffer-Moreira et al, 2014). As isoformas da placenta e do intestino são tecido-específicas e são expressas unicamente na placenta e no intestino, respectivamente, enquanto a isoforma do fígado-osso-rim é encontrada em quase todos os tecidos, sendo também denominada por esta razão de fosfatase alcalina não específica de tecido (TNAP).…”
Section: Fosfatase Alcalina (Tnap)unclassified
“…A comparação de parâmetros cinéticos (V m , K 0,5 , n, k cat entre outros) é complexa e requer metodologias com rígidos controles e condições ótimas de pH, espécie tamponante, presença de diferentes íons, entre outros. Porem, os parâmetros cinéticos podem ser utilizados para comparar a atividade de enzimas (Hoylaerts et al, 1997;Leone et al, 2005Leone et al, , 2012Simão et al, 2013;Kiffer-Moreira et al, 2014 (Segel, 1975).…”
Section: Cinética Enzimáticaunclassified